2006
DOI: 10.1111/j.1346-8138.2006.00147.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary cutaneous aggressive epidermotropic CD8+ cytotoxic T‐cell lymphoma with atypical presentation

Abstract: Primary cutaneous aggressive epidermotropic CD8 + cytotoxic T-cell lymphoma is characterized by a proliferation of epidermotropic CD8 + cytotoxic T cells and an aggressive clinical behavior. Patients present with localized or disseminated eruptive papules, nodules and tumors. We report a case of primary cutaneous aggressive epidermotropic CD8+ cytotoxic T-cell lymphoma with unusual clinical manifestation. The lesion occurred as multiple brownish macules and flat-topped papules on the hands, feet and face in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…[1][2][3][4][5][7][8][9][10][11][12][13][14][15][16][17] Clinically, the disease manifests as localized or disseminated papules, papules, nodules, and tumors, often with ulceration, hemorrhage, and necrosis, or with superficial hyperkeratotic patches and plaques. [1][2][3][4][5][7][8][9][10][11][12][13][14][15][16][17] Unlike classic MF, patients do not generally have long-standing precursor lesions and do not follow the typical progression through patch-, plaque-, and finally tumor-stage disease, but rather present from the onset with widespread plaque-and tumor-stage disease. 3,9,12 Involvement of mucosal surfaces, and acrally accentuated lesions of the palms and soles, is commonly seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][7][8][9][10][11][12][13][14][15][16][17] Clinically, the disease manifests as localized or disseminated papules, papules, nodules, and tumors, often with ulceration, hemorrhage, and necrosis, or with superficial hyperkeratotic patches and plaques. [1][2][3][4][5][7][8][9][10][11][12][13][14][15][16][17] Unlike classic MF, patients do not generally have long-standing precursor lesions and do not follow the typical progression through patch-, plaque-, and finally tumor-stage disease, but rather present from the onset with widespread plaque-and tumor-stage disease. 3,9,12 Involvement of mucosal surfaces, and acrally accentuated lesions of the palms and soles, is commonly seen.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,12 Involvement of mucosal surfaces, and acrally accentuated lesions of the palms and soles, is commonly seen. 3,4,9,10,13 Rapid progression with extracutaneous dissemination is typical, with metastasis to unusual sites including the lung, testis, central nervous system, and oral cavity, but generally sparing lymph nodes. 2,3,9,16,17 Santucci et al 8 have suggested that this pattern of metastasis may be related to CD56 positivity, which is commonly seen in aggressive CD8 1 T-cell lymphoma, J AM ACAD DERMATOL VOLUME 62, NUMBER 2 and which has been associated with homing to extranodal sites.…”
Section: Discussionmentioning
confidence: 99%
“…These include patient 25 reported by Massone et al 12 J AM ACAD DERMATOL the long course of the disease without any cutaneous or extracutaneous spread, and who responded completely to localized radiotherapy; these also include case 29 reported by Kim et al, 16 presenting asymptomatic, nonaggressive plane wartelike lesions in an otherwise healthy patient who refused any more investigation or treatment. Going with the same concept, the two cases reported by Gormley et al 26 cannot be considered as primary cutaneous aggressive epidermotropic CD8 1 lymphoma throughout the first year of presentation where there were single or very few indolent, nonaggressive lesions that did not affect the general health of the patient or cause metastatic spread.…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…[1][2][3][4][5][6] Because of the widespread and ulcerative nature of the lesions, patients usually seem in a bad general condition that may interfere with their usual daily activities. 3,6,19,23 Uncommonly, this aggressive tumor may present with superficial hyperkeratotic patches and plaques resembling clinically pagetoid reticulosis of the Ketron-Goodman type, 3 with widespread annular erythematous scaling patches 20 ; multiple maculopapular eruption on the hands, feet, and face 16 ; and pyoderma gangrenosumelike lesions. 23 HISTOPATHOLOGY Although the histopathologic features of primary cutaneous aggressive epidermotropic CD8 1 T-cell lymphoma are not pathognomonic, two constant features are always present, with variable extent, in all reported cases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…86 Recently, some groups have studied the prognosis of cutaneous involvement by NK/T-cell nasal and nasal type. 89,91,92,95,96 Metastases in unusual sites without spreading to the lymph nodes are also seen, such as to the testis, lung, oral cavity, or central nervous system. 87 Genomic differences have been found between cases of primary cutaneous extranodal NK/T-cell lymphoma and systemic NK/T-cell lymphoma with cutaneous involvement.…”
Section: Subcutaneous Panniculitis-like T-cell Lymphomamentioning
confidence: 99%